1994
DOI: 10.1136/bmj.309.6958.833
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of enalapril and   blockers in non- diabetic chronic renal failure

Abstract: In hypertensive patients with chronic renal failure enalapril slows progression towards end stage renal failure compared with beta blockers. This effect was probably not mediated through controlling blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
89
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(94 citation statements)
references
References 25 publications
3
89
0
2
Order By: Relevance
“…ACE inhibitors may be more effective than beta-blockers in slowing renal progression. 69 The dihydropyridine CCBs like nifedipine are not as effective as the non-dihydropyridine like verapamil or diltiazem in decreasing proteinuria. 70 In animal experiments co-administration of an ACE inhibitor and a CCB, verapamil, caused a more marked reduction in glomerulosclerosis and this was seen in the stroke-prone spontaneously hypertensive rat model even at non-antihypertensive doses.…”
Section: Black Hypertensive Patients With Renal Diseasementioning
confidence: 99%
“…ACE inhibitors may be more effective than beta-blockers in slowing renal progression. 69 The dihydropyridine CCBs like nifedipine are not as effective as the non-dihydropyridine like verapamil or diltiazem in decreasing proteinuria. 70 In animal experiments co-administration of an ACE inhibitor and a CCB, verapamil, caused a more marked reduction in glomerulosclerosis and this was seen in the stroke-prone spontaneously hypertensive rat model even at non-antihypertensive doses.…”
Section: Black Hypertensive Patients With Renal Diseasementioning
confidence: 99%
“…Calcium channel blockers (CCB) exert preferential vasodilation of afferent arterioles and may not reduce glomerular capillary pressure as efficiently as angiotensin-converting enzyme (ACE) inhibitors. 46,47 ACE inhibitors may be more effective than ␤-blockers in slowing progression of renal failure 48 and may achieve greater reduction in proteinuria than CCB. A study with a follow-up of 3 years showed that ESRD was more frequent in those treated with CCB compared to ACE inhibitors.…”
Section: Drug Treatmentmentioning
confidence: 99%
“…Both types can cause hyperkalemia. Beta-Adrenergic Blockers do not worsen renal function but, beyond blood pressure control, they do not protect the kidney (Hannedouche et al, 1994). Carvedilol is a Beta-Adrenergic Blocker with non-selective 1 activity that displays some advantages: beneficial effects on lipid profile (Stafylas & Sarafidis, 2008), increase of insulin sensitivity, and the capacity to reduce albumin excretion (Bakris et al, 2004).…”
Section: Which Drug Association Must We Favor?mentioning
confidence: 99%